ANALISIS KONSEP WISATA RELIGI PERSPEKTIF HUKUM EKONOMI SYARIAH - Muhammad Haidar Ali; Muhammad Nabat Ardli (Makkah: Journal Of Islamic Studies, 2025)
Religious tourism is a form of travel activity that combines both spiritual and economic Religious tourism is a form of travel activity that combines both spiritual and economic dimensions. In Indonesia, religious tourism has grown rapidly in various forms, such as pilgrimages to the graves of saints, visits to Islamic historical sites, and collective religious gatherings. However, practices in the field do not always reflect ideal Sharia-compliant values, particularly in terms of economic transactions, equitable distribution, and doctrinal purity. This study aims to analyze the concept of religious tourism from the perspective of Islamic economic law using a qualitative-descriptive approach and normative analysis method. Data were obtained from classical and contemporary fiqh muʿāmalah literature, fatwas issued by Indonesia’s National Sharia Council (DSN-MUI), and empirical studies on religious tourism practices in Indonesia. The analysis reveals that religious tourism is essentially permissible in Islam as long as it does not involve elements of shirk (polytheism), bidʿah (unwarranted innovation), or exploitation of the faithful. Principles of Islamic economic law, such as lawful transactions, justice, and public benefit (maṣlaḥah), must be the foundational basis for its management. The study identifies several deviations in practice, such as the commercialization of religious rituals and unjust economic benefit distribution. Therefore, strengthening of regulations, issuance of relevant fatwas, and public education are necessary to ensure that religious tourism becomes a means of Islamic propagation (daʿwah), preservation of Islamic culture, and economic empowerment of the Muslim community. This article contributes to expanding the scope of Islamic economic law into the tourism sector and provides a normative foundation for developing Sharia-compliant religious tourism based on maqāṣid al-sharīʿah.